Difficulties in Applying a Student-Centered Approach in Modern Russian Higher Education - O. V. Kisel; A. I. Dubskikh; A. V. Butova (Высшее образование в России)
The article attempts to define the application of student-centered approach in foreign language teaching at the Department of Foreign Languages in Engineering (Nosov Magnitogorsk State Technical University). The relevance of the research lies in the fact that it deals with a key issue of interest for teachers and educators as well as for teaching and learning process in general – the education of an active, creative, successful person, capable of self-development and self-improvement. Nowadays the theory of student-centered learning is rather rule than the exception in many educational institutions around the world. Nosov Magnitogorsk State Technical University follows modern educational trends. However, there are some difficulties in full realization of student-centered approach basic principles. The purpose of the research which included the survey of teachers and students on the conception of student-centered learning, was to identify and unleash the potential of a student-centered approach in foreign language learning at a university. The authors concluded that respondents are not fully aware of this approach. The results of self-reflection observations are manifested in the form of various limitations. These limitations are associated with students and teachers. The most important limitations are connected with the lack of motivation for students to study. The practical significance of the research is that its findings can be taken into account when eliminating difficulties in introducing student-centered approach in teaching foreign languages and other disciplines at a university.